MUTUAL RECOGNITION OF JUDICIAL DECISIONS AND THE RIGHT TO A FAIR TRIAL WITH SPECIAL FOCUS ON THE ECHR’S FINDINGS IN THE CASE OF AVOTIŅŠ V. LATVIA (EU and comparative law issues and challenges series (ECLIC), 2018)
In Avotiņš v. Latvia, the European Court of Human Rights (from now on: ECHR; Court) was questioning whether the Conventional right to a fair trial applies in cases of mutual recognition of judicial decisions on EU level. Without dealing with errors of fact or law allegedly made by a national court, the Court found it necessary to determine whether the national court has infringed the rights and freedoms protected by the Convention. Although the applicant claimed that the national court breached the Brussels I Regulation and thus violated the right to a fair trial, the ECHR concluded that it is not up to the Court to decide on the compliance of national law with international treaties and EU law. As it can be understood from the judgment, the ECHR holds that interpretation and application of the provisions of the EU regulations fall under the jurisdiction of the national courts and the Court of Justice of the European Union (from now on: the CJEU). However, the ECHR reaches a conclusion that the Contracting States are obliged to take care of the parties’ procedural rights when applying the EU law for the reason that provisions of the EU law must not be applied mechanically, without bearing in mind the duty of taking into account the rights protected by the Convention. In this paper, the authors shall analyze the relationship between the ECHR and the CJEU taking into account and resorting to the ECtHR’s findings in the case of Avotiņš v. Latvia.